Kajian Pemasaran Dengan Pendekatan SCP Pada Agroindustri Selai Nanas Goreng Di Kabupaten Muaro Jambi - Sariani, Sariani; Alamsyah, Zulkifli; Yanita, Mirawati (Universitas Batangahari Jambi, 2024)
This study aims to: 1) Describe the general overview of the fried pineapple jam agroindustry business in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency, 2) Describe the general overview of the marketing of fried pineapple jam agroindustry in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency, 3) Analyze the market structure in the fried pineapple jam agroindustry in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency, 4) Analyze market behavior in the fried pineapple jam agroindustry in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency, and 5) Analyze market performance in the fried pineapple jam agroindustry in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency. The sampling method in this study was carried out purposively (intentionally) to the fried pineapple jam agroindustry in Tangkit Baru Village. The scope of the research is limited to the marketing of fried pineapple jam agroindustry using the Structure, Conduct and Performance (SCP) approach. The results of the study showed: 1) The fried pineapple jam agroindustry in Tangkit Baru Village is a household business that is generally managed to increase added value, 2) The fried pineapple jam marketing channel formed consists of 2 marketing channels, namely: (1) agro-industry-consumer; and (2) Agro-industry-retailer-consumer and each institution performs the function of marketing functions including exchange functions, physical functions and facility functions, 3) Fried pineapple jam agroindustry has a strict oligopoly market structure, 4) Market behavior is characterized by the implementation of price strategies, products, promotions and is a capital-intensive agroindustry, and 5) The market performance of the agro-industry of fried pineapple jam is not good with low X-eff and PCM values obtained..